Le site d'information The Conversation France comme ressource pédagogique - Julien Falgas (Centre National d'Enseignement à Distance, 2017)
The Conversation France has been online since September 2015. As an information media, it takes the form of a website dedicated to scientific and common news. Academics and journalists collaborate to write and publish articles together, in order to share and spread academic knowledge. Could The Conversation France contribute to a new kind of school mediation, and help academic and school worlds to meet ? In an observer-participant position (he coordinates the The Conversation France project for the University of Lorraine), the author of this action-research refers to field data, a readership survey and interviews with academic authors, journalists and junior school librarians teachers. The analysis suggests that the teachers might need the contents of The Conversation France to be acknowledged and re-mediated, so that they feel fully receivers on a professional basis.